Clinical characteristics of patients with diffuse alveolar hemorrhage diagnosed by cytological examination of 1000 bronchoalveolar lavage samples - Prasad, Pallavi; Gupta, Aviral; Nath, Alok; Hashim, Zia; Gupta , Mansi; Krishnani, Narendra; Khan, Ajmal (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: Diffuse alveolar hemorrhage (DAH) is a life-threatening condition due to the extravasation of blood in the alveoli, resulting in hypoxemia and even acute respiratory distress syndrome. This study aimed to describe the clinico-radio-pathological profile of patients diagnosed with DAH and classify it into immune and nonimmune DAH. Methods: This was a retrospective analytical study. Of a total of 1000 cases of bronchoalveolar lavage fluids (BALF) received for cytological examination, patients fulfilling the clinical, radiological, and laboratory details of cases satisfying the clinical and cytological criteria of DAH (n=47) were studied. Results: The most common cause of immune DAH was ANCA-associated vasculitis (n=13, 27.6%), and that of nonimmune DAH was infections (n=10, 21.3%). Twenty-nine patients (61.7%) had hemoptysis. The most common radiological finding was ground-glass opacities (n=33, 70.2%). In univariate analysis, female sex, mean hemoglobin at admission, total leucocyte count (TLC), platelet count, and erythrocyte sedimentation rate (ESR) were significantly associated with immune-DAH. However, in multivariate analysis, female sex, higher TLC, high platelets, and high ESR were significantly associated with immune DAH. Patients were treated with corticosteroids (n=25, 46.3%), intravenous cyclophosphamide (n=12, 22.2%), plasma exchange (n=7, 13.0%), intravenous immunoglobulin (n=5, 9.3%) and rituximab (n=5, 9.3%). The overall mortality was 8.5% (n=4). Conclusions: DAH is a life-threatening syndrome that may be classified into immune and nonimmune DAH. Immune-DAH requires aggressive management, whereas nonimmune DAH cases respond best to conservative management.